Gender Particularities of Value Ideals of Chiefs - Bocheliuk, Vitalii I.; Panov, Nikita S.; Fedorenko, Myroslav I.; Zhuzha, Lilia A.; Cherepiekhina, Olha A. (Prabandhan: Indian Journal of Management, 2019)
The research work substantiated the relevance of studying the individual values of chiefs as the creators of organizational culture, which affect the socialization of a wide range of Ukrainian adults. The gender particularities of the content and structure of the value orientation of the private business chiefs were described in detail (data of comparative research of 39 respondents with the help of the Schwartz Personal Values Questionnaire). A significant difference in the evaluation of such basic motivational tendencies as "Power," "Hedonism," and "Tradition" were proved and the differences in the structural organizing of the value hierarchy of different representatives was also shown. The lists of terminal and instrumental values of chiefs were analyzed in detail and the leading tendencies in accordance with the gender status were also singled out. The structure of correlations between the value types was identified individually in the male and female respondents of the sample, demonstrating radical differences. A new scientific discovery that requires further development and verification was found as well as the gender differences in the realization of the desire to get sensual satisfaction and structurally organizing the values according to sex were identified.